Saving with Group or Individual Personal Pension Schemes: How Much Difference Does It Make? - Zalewska, Anna (Ania) (Management Science, 2022)
The quality of services provided by institutional investors has attracted considerable attention. This paper adds to the debate by showing that institutional differences in setting up defined contribution personal schemes have an economically and statistically significant impact on the returns. Using a sample of 10,326 UK defined contribution personal pension funds over July 1990–June 2019, I show that pension funds that have a third party involved in contract setting and subsequent oversight deliver 0.96%–1.67% higher gross returns and charge 0.7% lower fees than pension funds offered directly to the public without any well-informed third party involved. I also show that the introduction of additional governance bodies in 2015 resulted in a widening of the performance gap, which further supports the notion that investment governance has a material impact on fund performance. The results highlight the importance of investment oversight and call for more protection for individual investors. This paper was accepted by Tomasz Piskorski, finance.